X²-x-1=a a(a-6)+5<0 a²-6a+5<0 a1+a2=6 U a1*a2=5⇒a1=1 U a2=5 1<a<5 1)x²-x-1>1 x²-x-2>0 x1+x2=1 U x1*x2=-2⇒x1=-1 U x2=2 x<-1 U x>2 2)x²-x-1<5 x²-x-6<0 x1+x2=1 U x1*x2=-6⇒x1=-2 U x2=3 -2<x<3 x∈(-2;-1) U (2;3)
x4−2x3−7x2+8x+7<−5x4−2x3−7x2+8x+7+5<0x4−2x3−7x2+8x+12<0Решить данное неравенство невозможно, т.к. многочлен в левой части не первой ( Ax+B ) и не второй степени ( Ax2 + Bx + C ).
a(a-6)+5<0
a²-6a+5<0
a1+a2=6 U a1*a2=5⇒a1=1 U a2=5
1<a<5
1)x²-x-1>1
x²-x-2>0
x1+x2=1 U x1*x2=-2⇒x1=-1 U x2=2
x<-1 U x>2
2)x²-x-1<5
x²-x-6<0
x1+x2=1 U x1*x2=-6⇒x1=-2 U x2=3
-2<x<3
x∈(-2;-1) U (2;3)